Intestinal protozoan infections shape fecal bacterial microbiota in children from Guinea-Bissau. - Sebastian von Huth; Louise B Thingholm; Poul-Erik Kofoed; Corinna Bang; Malte C Rühlemann; Andre Franke; Uffe Holmskov (Public Library of Science (PLoS), 2021)
Intestinal parasitic infections, caused by helminths and protozoa, are globally distributed and major causes of worldwide morbidity. The gut microbiota may modulate parasite virulence and host response upon infection. The complex interplay between parasites and the gut microbiota is poorly understood, partly due to sampling difficulties in remote areas with high parasite burden. In a large study of children in Guinea-Bissau, we found high prevalence of intestinal parasites. By sequencing of the 16S rRNA genes of fecal samples stored on filter paper from a total of 1,204 children, we demonstrate that the bacterial microbiota is not significantly altered by helminth infections, whereas it is shaped by the presence of both pathogenic and nonpathogenic protozoa, including Entamoeba (E.) spp. and Giardia (G.) lamblia. Within-sample diversity remains largely unaffected, whereas overall community composition is significantly affected by infection with both nonpathogenic E. coli (R2 = 0.0131, P = 0.0001) and Endolimax nana (R2 = 0.00902, P = 0.0001), and by pathogenic E. histolytica (R2 = 0.0164, P = 0.0001) and G. lamblia (R2 = 0.00676, P = 0.0001). Infections with multiple parasite species induces more pronounced shifts in microbiota community than mild ones. A total of 31 bacterial genera across all four major bacterial phyla were differentially abundant in protozoan infection as compared to noninfected individuals, including increased abundance of Prevotella, Campylobacter and two Clostridium clades, and decreased abundance of Collinsella, Lactobacillus, Ruminococcus, Veillonella and one Clostridium clade. In the present study, we demonstrate that the fecal bacterial microbiota is shaped by intestinal parasitic infection, with most pronounced associations for protozoan species. Our results provide insights into the interplay between the microbiota and intestinal parasites, which are valuable to understand infection biology and design further studies aimed at optimizing treatment strategies.